Exploring Client-Centered Care Experiences in In-Patient Rehabilitation Settings - Elena L. Bamm; Peter Rosenbaum; Seanne Wilkins; Paul Stratford; Nadilein Mahlberg (SAGE Publishing, 2015)
Patient or client-centered care has been widely accepted as an essential component of health care delivery in many countries. Few studies explore actual implementation of client-centered principles and clients' and health care providers' (HCPs) experiences with these approaches. Our objective was to explore current models of delivery of rehabilitation services from the perspectives of patients, families, and HCPs. We conducted semistructured interviews with patients, families, and HCPs of one of four rehabilitation facilities in South-Central Ontario, Canada. Being on common grounds/Working toward client set goals was the main category identified by both clients and HCPs. Although successful partnerships were created, the majority of clients assumed a passive position. Clients needed more information about the rehabilitation progression and alternative treatment options. The results of the study suggest that we need to encourage and educate clients to become motivated, well-informed, proactive participants in their care.